PENGEMBANGAN SISTEM SMS GATEWAY UNTUK PENGIRIMAN INFORMASI PERKULIAHAN KE JEJARING SOSIAL MENGGUNAKAN RASPBERRY PI - , ARIF WAHYUDI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Short Message Service (SMS) is one of the favorite features and the most commonly used by cell phone users. SMS can be used to send and receive information, such as information about the course. To facilitate the dissemination of information, SMS Gateway system was built which makes sending and receiving SMS contains with information processed automatically. In addition, the development of internet based social networks also influence the way people interact and send information. Social networking has now become the place to share and get information quickly. The emergence of Raspberry Pi as a credit-card sized computer that can work like a regular desktop computer and can be implemented in a various purposes, such as a SMS Gateway server. This study aimed to develop a system of SMS Gateway on Raspberry Pi that can receive the course information from SMS then forwards it to a social network account like Facebook and Twitter. Based on the implementation and testing results, it can be concluded that the system is able to receive an SMS contains information about courses, stores to database and forwards them to social network, Facebook and Twitter.